Manajemen Sumber Daya Manusia Sebagai Pilar Strategis Dalam Pengelolaan Lembaga Pendidikan - Indah Wahyuni (Prodi. Manajemen Pendidikan Islam, Fakultas Tarbiyah, Institut Pesantren Sunan Drajat, 2023)
This study aims to analyze the strategic role of human resource management (HRM) in enhancing the effectiveness and competitiveness of educational institutions. Using the library research method, this study collected, reviewed, and synthesized various relevant sources, including books, national and international journal articles, and policy documents related to HRM and educational management. The results indicate a paradigm shift in HRM from a merely administrative function to a strategic role integrated with the institution’s vision and mission. The key findings highlight four main aspects: (1) HRM as a strategic instrument supporting innovation and organizational change; (2) continuous professional development for educators and education staff as a critical factor in improving quality; (3) the implementation of competency-based performance appraisals and fair reward systems to foster a productive and innovative work culture; and (4) the integration of HRM policies into institutional strategies to enhance organizational resilience. This study concludes that HRM serves as a strategic pillar that not only supports operational processes but also becomes a crucial factor in shaping educational institutions to be adaptive, professional, and competitive in the global era.